2008
DOI: 10.1172/jci34676
|View full text |Cite
|
Sign up to set email alerts
|

Immune tolerance improves the efficacy of enzyme replacement therapy in canine mucopolysaccharidosis I

Abstract: Mucopolysaccharidoses (MPSs) are lysosomal storage diseases caused by a deficit in the enzymes needed for glycosaminoglycan (GAG) degradation. Enzyme replacement therapy with recombinant human α-l-iduronidase successfully reduces lysosomal storage in canines and humans with iduronidase-deficient MPS I, but therapy usually also induces antibodies specific for the recombinant enzyme that could reduce its efficacy. To understand the potential impact of α-l-iduronidase-specific antibodies, we studied whether induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
127
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(135 citation statements)
references
References 24 publications
4
127
2
2
Order By: Relevance
“…Patients treated with ERT show clinical improvement of somatic manifestations and improved quality of life (QOL). However, there are several limitations with current ERT: i) limited effect on skeletal symptoms [15][16] ii) rapid clearance from the circulation, and iii) immunological issues (antibody production leads to reduced therapeutic efficacy) [7,[17][18][19]. To resolve the above issues, a long circulating or bone-targeting enzyme was devised to deliver the enzyme to bone [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Patients treated with ERT show clinical improvement of somatic manifestations and improved quality of life (QOL). However, there are several limitations with current ERT: i) limited effect on skeletal symptoms [15][16] ii) rapid clearance from the circulation, and iii) immunological issues (antibody production leads to reduced therapeutic efficacy) [7,[17][18][19]. To resolve the above issues, a long circulating or bone-targeting enzyme was devised to deliver the enzyme to bone [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…7 More recent studies in canine models of MPSI demonstrated up to 90% inhibition of enzyme uptake by MPSI fibroblasts by serum taken from dogs that had high titer anti-IDUA antibodies. 8 There is increasing evidence, mostly derived from animal models of LSD, of an inverse correlation between an observed antibody response and metabolic and clinical outcome. Even though the immune response currently reported in patients with MPSI is 91%, 9 the true incidence of functionally active (neutralizing) antibodies is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the canine model of MPS I have demonstrated that ADA can alter the distribution and effectiveness of ERT at the tissue level, and that immune tolerizing regimens can prevent ADA formation and improve the effectiveness of ERT as shown by enhanced enzyme activity in critical target tissues as compared to the enzyme activity in such tissues in non-tolerant dogs [27]. Moreover, in murine KO models of Fabry Disease, ERT activity was dramatically decreased in target tissues in seropositive as opposed to seronegative animals.…”
mentioning
confidence: 99%